ESCHERICHIA COLI: AN IMPORTANT PATHOGEN IN PATIENTS WITH HEMATOLOGIC MALIGNANCIES - Daniel Olson; Abraham Tareq Yacoub; Gelenis Domingo; John Norman Greene (Mediterranean Journal of Hematology and Infectious Diseases)
Abstract